2017
DOI: 10.1590/1982-0194201700038
|View full text |Cite
|
Sign up to set email alerts
|

Educação em Enfermagem: conceituando projeto pedagógico na visão de professores

Abstract: Objective: To understand the pedagogical project concept of the professors of the Paulista School of Nursing, and to identify the challenges and the limits faced by them during its development. Methods: Qualitative study, in the oral history thematic modality. Using semi-structured interviews, the narratives of six professors who participated in, at least, half of the meetings for the pedagogical development were obtained. The statements were recorded, interpreted text transcribed, recreated and analyzed, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
5

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
0
3
0
5
Order By: Relevance
“…The reflections from this approach allow for a critical analysis of the pedagogical projects of courses that establish contents in subjects with little articulation between theory and practice, that value the results and not the learning process, given that factors like these can imply difficulties in the translation of knowledge. 18,19 In addition, the environment itself may participate in learning as a challenge to be faced by the students, and compromise the development of their skills. This is evidenced when the field of practice and the educational institution are not properly articulated in relation to the development of the internship, and when the supervisors are not prepared to receive the student, in such cases there is a gap between theory and hospital practice, which causes insecurity and little autonomy for students.…”
Section: Discussionmentioning
confidence: 99%
“…The reflections from this approach allow for a critical analysis of the pedagogical projects of courses that establish contents in subjects with little articulation between theory and practice, that value the results and not the learning process, given that factors like these can imply difficulties in the translation of knowledge. 18,19 In addition, the environment itself may participate in learning as a challenge to be faced by the students, and compromise the development of their skills. This is evidenced when the field of practice and the educational institution are not properly articulated in relation to the development of the internship, and when the supervisors are not prepared to receive the student, in such cases there is a gap between theory and hospital practice, which causes insecurity and little autonomy for students.…”
Section: Discussionmentioning
confidence: 99%
“…A mesma preocupação pela qualificação do ensino é comentada por Q19: "A teoria é a base de tudo, fundamenta todos os estudos realizados na área, inclusive esse estudo servirá para melhorar o ensino, e isso que precisamos de forma que nos formemos melhor no final". A qualificação do ensino parte integralmente da condução linear da teoria e prática em aplicação pelo estudante, e segundo Magalhães et al (2017), a repercussão dessa junção traz a tona a reflexão crítica dos envolvidos, tornando-os capacitados.…”
Section: A Construção De Conceitos: a Percepção Dos Estudantes Sobre A Relação Entre Teoria E Práticaunclassified
“…Para Magalhães et al (2017), as práticas estão previstas nas Diretrizes Curriculares vista a sua importância para a formação do estudante, e principalmente para que desenvolvam suas capacidades, tidas como de iniciativa individual, incluindo a perspectiva de atuação profissional.…”
Section: A Construção De Conceitos: a Percepção Dos Estudantes Sobre A Relação Entre Teoria E Práticaunclassified
See 1 more Smart Citation
“…A research on a nursing course at a federal institution of São Paulo showed that curriculum was presented by a list of courses organized in a hierarchical manner with isolated content. Such an organization is associated with the professors' lack of preparation regarding pedagogical knowledge to guide the elaboration of PPP with their own identity, thus breaking with the traditional teaching paradigm (28) .…”
Section: Labyrinths Of Nursing Training and The Brazilian National Mementioning
confidence: 99%